ChemInform Abstract: C‐Cinnamoyl Glycosides as a New Class of anti‐Filarial Agents. Issue 32 (22nd July 2016) - Roy, Priya; Dhara, Debashis; Parida, Pravat Kumar; Kar, Rajiv Kumar; Bhunia, Anirban; Jana, Kuladip; Sinha Babu, Santi P.; Misra, Anup Kumar
Abstract: A series of C‐cinnamoyl glycosides are synthesized by the BF3 ·OEt2 ‐catalyzed aldol condensation of aromatic aldehydes with glycosylated acetones.